2016
DOI: 10.1016/j.seares.2016.09.002
|View full text |Cite
|
Sign up to set email alerts
|

Deeply hidden inside introduced biogenic structures – Pacific oyster reefs reduce detrimental barnacle overgrowth on native blue mussels

Abstract: In sedimentary coastal ecosystems shells of epibenthic organisms such as blue mussels (Mytilus edulis) provide the only major attachment surface for barnacle epibionts, which may cause detrimental effects on their mussel basibionts by e.g. reducing growth rate. In the European Wadden Sea, beds of native blue mussels have been invaded by Pacific oysters Crassostrea gigas, which transformed these beds into mixed reefs of oysters with mussels. In this study, we determined the spatial distribution of M. edulis and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5
2
1

Relationship

5
3

Authors

Journals

citations
Cited by 23 publications
(22 citation statements)
references
References 51 publications
0
22
0
Order By: Relevance
“…Furthermore, below the canopy of oysters, detrimental overgrowth by barnacles on mussels was low relative to exposed positions (Buschbaum et al. ). This may help mussels to overcome curtailed food in the association with oysters above them.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, below the canopy of oysters, detrimental overgrowth by barnacles on mussels was low relative to exposed positions (Buschbaum et al. ). This may help mussels to overcome curtailed food in the association with oysters above them.…”
Section: Discussionmentioning
confidence: 99%
“…These behavioral traits may not only determine the persistence of mussel beds in different habitats, but also their resistance to invaders (Buschbaum et al, 2016) or their own invasion success as shown in the Mediterranean mytilid mussel M. galloprovincialis (Branch and Steffani, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…by increasing hydrodynamic forces for an overgrown individual (e.g. see Laudien and Wahl, 1999;Buschbaum and Saier, 2001;Buschbaum et al, 2016). Therefore, mussels seeking byssus attachment sites may prefer clean conspecifics.…”
Section: Introductionmentioning
confidence: 99%
“…Currently, the number of non-indigenous species still seems low (39 out of 2758 equivalent to 1.4%) but some of the introduced species already had fundamental effects on the communities [41]. Examples are American razor clams Ensis leei which became a dominant bivalve in terms of abundance and biomass in the subtidal zone of the Wadden Sea [42], Pacific oysters Magallana (Crassostrea) gigas which turned the former mussel (Mytilus edulis) beds into combined oyster/mussel beds [43,44], or the Japanese seaweed Sargassum muticum which forms extensive beds in the shallow subtidal zone and nowadays functionally replaces former native seagrass (Zostera marina) beds that almost went extinct in the 1930s due to a parasitic slime mould [45] and failed to recover to their original extension, up to now. Most of the non-indigenous species recorded so far are either planktonic or large benthic species.…”
Section: Total Speciesmentioning
confidence: 99%